In vitro interaction between plasmodium falciparum myosin B (PfMyoB) and myosin a tail interacting protein (MTIP) (2018)
Apicomplexan parasites, including Plasmodium falciparum, are obligate intracellular organisms that utilize a strategy termed “gliding” to move and invade host cells, causing disease. Gliding is carried out by a protein complex known as the glideosome, which includes an actin–myosin motor. To date, six myosins have been identified in P. falciparum (PfMyoA, B, C, D, E, and F), but only the role of PfMyoA, the myosin of the glideosome that is involved in the process of red blood cell and mosquito cell invasion, has been established. Based on previous observations, we speculated that PfMyoA and PfMyoB may have similar or redundant functions. To test this hypothesis, we searched for in vitro interactions between PfMyoB and MTIP (myosin A tail interacting protein), the myosin light chain of PfMyoA. A set of differentially tagged PfMyoA, PfMyoB, and MTIP recombinant proteins was employed to specifically and simultaneously detect each myosin in competition assays and inhibition assays using specific peptides. MTIP potentially acts as the light chain of PfMyoB.